Samorząd w myśli Feliksa Konecznego - Polak, Ryszard (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article contains an analysis of Feliks Koneczny’s views on local governments and the necessary conditions for its functioning. According to him, their development is only possible in Latin civilization, as it alone allows the active participation of all members of the state community in social and professional life without discriminating them. Its foundations are based on the Catholic personalist worldview, according to which every person is treated as a full member of the community with all his rights and duties. Non-personalistic civilizations originating from other philosophical traditions and created in other social and historical conditions than Latin civilization limit human freedom. Participation of the individual in social life is limited, and self-government in practically non-existent.
Keywords: administracja państwowa; samorząd; cywilizacja; prawo; biurokracja; totalitaryzm; autorytaryzm